Reconstructing neural circuits using multiresolution correlated light and electron microscopy - Friedrichsen, Karl; Ramakrishna, Pratyush; Hsiang, Jen-Chun; Valkova, Katia; Kerschensteiner, Daniel; Morgan, Josh L. (Frontiers in Neural Circuits, 2022)
Correlated light and electron microscopy (CLEM) can be used to combine functional and molecular characterizations of neurons with detailed anatomical maps of their synaptic organization. Here we develop a multiresolution approach to CLEM (mrCLEM) that efficiently targets EM imaging to optically characterized cells while maintaining the optimal tissue preparation for high-throughput EM reconstruction. This approach hinges on the ease with which arrays of sections collected on a solid substrate can be repeatedly imaged at different scales using scanning electron microscopy. We match this multiresolution EM imaging with multiresolution confocal mapping of the aldehyde fixed tissue of interest. Features visible in lower resolution EM correspond well to features visible in densely labeled optical maps of fixed tissue. Iterative feature matching, starting with gross anatomical correspondences and ending with subcellular structure, can then be used to target high-resolution EM image acquisition and annotation to cells of interest.